A new survey of paleomagnetic directions in the Miocene lava pile between Arnarfjörður and Breiðafjörður in the Vestfirðir peninsula, Northwestern Iceland (Dataset) ... - Kristjánsson, Leó (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: A new survey of paleomagnetic directions in the Miocene lava pile between Arnarfjörður and Breiðafjörður in the Vestfirðir peninsula, Northwestern Iceland ...